2017
DOI: 10.26417/ejser.v9i2.p67-72
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Motivation on the Quality of the Leader – Follower Relationship

Abstract: The subject of this research is the connection of the motivational structure with the quality of the leaderfollower relationship. The aim is to determine the ways to improve the quality of the leader -fololower relationship which will consequently enhance the productivity and the satisfaction of employees. The research results have shown that the motivational factors, such as reward systems, good interpersonal relationships, career development possibilities and good team spirit, are significantly statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Odgovori ispitanika kreću se od 1−uopšte se ne slažem do 5−potpuno se slažem, a viši skor na ovoj skali označava veće slaganje sa navedenim tvrdnjama. Tvrdnja 2,4,6,8,10,12,14,16,18,19,21,23,24,26,29,31,32, U odnosu na mesto gde ispitanici žive (Tabela 5), na dimenziji opšte zadovoljstvo poslom najviši skor je dobijen kod ispitanika iz Srbije (AS=3,24, SD=0,145), a najniži skor kod ispitanika koji žive u Rusiji (AS=3,07, SD=0,208). Na dimenziji zadovoljstvo trenutnim poslom, najviši skor je dobijen kod ispitanika koji žive u EU (AS=3,65, SD=0,359), a najmanji skor kod ispitanika iz Srbije (AS=3,28, SD=0,272).…”
Section: Pouzdanost Korišćenih Instrumenataunclassified
“…Odgovori ispitanika kreću se od 1−uopšte se ne slažem do 5−potpuno se slažem, a viši skor na ovoj skali označava veće slaganje sa navedenim tvrdnjama. Tvrdnja 2,4,6,8,10,12,14,16,18,19,21,23,24,26,29,31,32, U odnosu na mesto gde ispitanici žive (Tabela 5), na dimenziji opšte zadovoljstvo poslom najviši skor je dobijen kod ispitanika iz Srbije (AS=3,24, SD=0,145), a najniži skor kod ispitanika koji žive u Rusiji (AS=3,07, SD=0,208). Na dimenziji zadovoljstvo trenutnim poslom, najviši skor je dobijen kod ispitanika koji žive u EU (AS=3,65, SD=0,359), a najmanji skor kod ispitanika iz Srbije (AS=3,28, SD=0,272).…”
Section: Pouzdanost Korišćenih Instrumenataunclassified
“…Bobera, Jelaca and Bjekic (2017) [1] came to the conclusion that a combination of transactional and transformational leadership style is present in Serbian companies, while laissez faire leadership is almost unrecognizable. Simic, Kezic, and Ristic (2017) [16] observed connection of the motivational structure with the quality of the relationship between leader and employees. Stojanovic-Aleksic, Stamenkovic, and Milanovic (2016) [18] investigated the relationship between gender leadership and leadership style applied by the leader and concluded that women leaders are more taskoriented and implement an authoritarian leadership style while men choose democratic leadership styles.…”
mentioning
confidence: 99%